Risk, resilience, and positive youth development developing effective community programs for at-risk youth : lessons from the Denver Bridge Project - Jenson, Jeffrey M. (New York ; Oxford : Oxford University Press, 2013)
This title describes an approach to developing and testing effective community-based programmes for at-risk children and youth. The book shows how elements of risk and resilience positive youth development, and organizational collaboration are used to develop a comprehensive intervention framework called the Integrated Prevention and Early Intervention (IPEI) Model.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Youth -- Services for -- United States; Problem youth -- United States